2013
DOI: 10.1007/s10162-013-0399-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Systemic Toxicity and Preserved Vestibular Toxicity Following Co-treatment with Nitriles and CYP2E1 Inhibitors: a Mouse Model for Hair Cell Loss

Abstract: Several nitriles, including allylnitrile and ciscrotononitrile, have been shown to be ototoxic and cause hair cell degeneration in the auditory and vestibular sensory epithelia of mice. However, these nitriles can also be lethal due in large part to the microsomal metabolic release of cyanide, which is mostly dependent on the activity of the 2E1 isoform of the cytochrome P450 (CYP2E1). In this study, we co-administered mice with a nitrile and, to reduce their lethal effects, a selective CYP2E1 inhibitor: diall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…In most control specimens ( Fig. 2A), the appearance and density of the stereociliary bundles matched the literature descriptions for epithelia from healthy adult rats and mice (Dechesne et al, 1986;Soler-Martín et al, 2007;Saldaña-Ruíz et al, 2013), and were given a pathology score of 0. Nevertheless, some control samples attained SEM Pathology Scores of 1 or 2, as they displayed blebs or stererociliary fusion in a small number of HCs, respectively.…”
Section: Sem Analysis Of Stereociliary Damage and Hc Loss Following Smentioning
confidence: 54%
See 1 more Smart Citation
“…In most control specimens ( Fig. 2A), the appearance and density of the stereociliary bundles matched the literature descriptions for epithelia from healthy adult rats and mice (Dechesne et al, 1986;Soler-Martín et al, 2007;Saldaña-Ruíz et al, 2013), and were given a pathology score of 0. Nevertheless, some control samples attained SEM Pathology Scores of 1 or 2, as they displayed blebs or stererociliary fusion in a small number of HCs, respectively.…”
Section: Sem Analysis Of Stereociliary Damage and Hc Loss Following Smentioning
confidence: 54%
“…Except for cis-2-pentenenitrile (Saldaña-Ruíz et al, 2012a), human exposure is unlikely or very low (Tanii et al, 2004). Nevertheless, their use to study ototoxicity phenomena is supported by the many identified similarities between nitrile and aminoglycoside ototoxicity, and their greater dependency of use in rodent models (Soler-Martín et al, 2007;Saldaña-Ruíz et al, 2013;Sedó-Cabezón et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the known combinations of common features and species-specific differences in vestibular histology and physiology (Boyle et al, 1992;Curthoys et al, 2017;Desai et al, 2005a,b;Eatock, 2018;Goldberg, 2000), it would be premature to assume that a similar relationship between tail-lift angles and HC loss will occur in the mouse as in the rat. Although ventral curling during tail-lift has been reported in many vestibular-deficient mice, our observations after vestibular toxicity in rats (Llorens et al, 1993;Llorens and Rodríguez-Farré., 1997;Martins-Lopes et al, 2019; this study) and mice (Soler-Martin et al, 2007;Saldaña-Ruíz et al, 2013;Boadas-Vaello et al, 2017;Greguske et al, 2019) suggest that the abnormal tail-lift response develops more easily and robustly in the former than the latter species.…”
Section: Discussionmentioning
confidence: 62%
“…Rats receiving 1.5, 1.75, and 2.0 mmol / kg of cis-2-pentenenitrile displayed reduced rearing activity in the open field and increased rating scores on the vestibular dysfunction test battery as well as hair cell loss (1-3, 1-4, and 3-4 vestibular ratings as compared with control (0-1) 12) . Dose-response studies on allyl showed the match between behavioral effects and hair cell loss in mice 21) . In addition, it is reported that behavioral effects, observed in animals administered 3,3 'iminodipropionitrile (400, 600, and 1000 mg/kg) or crotononitrile (250 mg/kg), are identical to those observed in mutant mice lacking vestibular function and in rodents with bilateral labyrinthectomy 13,14 ) .…”
Section: Toxicitymentioning
confidence: 96%